Agrobacterium-Mediated Stable Transformation of Medicinal Plant Andrographis paniculata Callus Expressing Î²-glucuronidase (GUS) Gene - Marwani, Erly; Tangapo, Agustina; Dwivany, Fenny Martha (Indonesian Journal of Biotechnology, 2013)
This study was carried out to establish a stable genetic transformation in callus culture of Andrographispaniculata mediated by Agrobacterium tumefaciens. The leaf disks of A. paniculata were infected with A. tumefaciensLBA4404 carrying a binary vector pCAMBIA1304 that contain β-glucuronidase (GUS) and hygromycinphosphotransferase (hpt) genes. The infection was conducted by dipping method for one hour, followed byco-cultivation in the dark for three days. To examine transient GUS expression, the co-cultivated leaf disks wereassayed for β-glucuronidase activity and to obtain stable transformed callus, the co-cultivated leaf disks wereselected on the callus induction medium which contain 20 mg/l hygromycin for selection. The transformedcallus was periodically subcultured every three weeks into the fresh selection medium over the 15 weeksperiod. To test a stable transformation, the callus was subjected to PCR analysis for GUS gene detection. Theresults indicated that the co-cultivated leaf disks expressed GUS activity and proliferated to produce callus onthe selective medium. Analysis of PCR on the transformed callus indicated the presence 976 bp fragment thatconfi rmed the presence of β-glucuronidase gene. These fi ndings imply that the β-glucuronidase was stablyintegrated into A. paniculata callus culture.Keywords: Andrographis paniculata, Agrobacterium tumefaciens, andrographollide, transformed callus,β-glucuronidase gene.